Combined effect of pediocin bacHA-6111-2 and high hydrostatic pressure to control listeria innocua in fermented meat sausage - Castro, S. M. (2018)
In and ex situ production of bacteriocin (bacHA-6111-2) combined with high hydrostatic pressure (300 MPa, 5 min, 10ºC) were assessed on the survival of Listeria innocua reviously inoculated in Alheira, a traditional Portuguese fermented meat product. The effect was evaluated immediately after each treatment, alone and combined, and during 60 days of storage (4ºC). For higher concentrations of L. innocua, a bacteriostatic effect was verified: i) during the first days of storage for the pressure treatment alone and in combination with ex situ production of bacteriocin; and ii) for longer periods, when pressure was combined with in situ production of bacteriocin. After this effect, the first treatments revealed rapid growth up to the initial values; while the latest treatment, and for lower initial cells, resulted in a decrease > 2 log CFU g-1, from day 3 of storage until the end of the study. A similar result was obtained for analogous pressurized L. innocua samples with ex situ production of bacteriocin. The developed work has demonstrated the potential of using the combination of natural antimicrobial compounds (pediocin bacHA-6111-2, produced either in or ex situ) with mild pressure (300 MPa, 5 min) treatments to control effectively L. innocua in fermented meat products such as Alheiras, when contaminated with values closed to the ones that might potentially arise by natural postcontamination.